Pengaruh Pelaksanaan Pembelajaran Kooperatif Tipe STAD Terhadap Kemampuan Kerjasama Siswa SDN 94 Balla Kabupaten Enrekang - A Lambogo; Evy Segarawati Ampry; Nadir; Syahidah Rahmah (Universitas Sulawesi Barat, 2023)
This study aims to (1) obtain an overview of the implementation of cooperative learning type STAD (2) to get a picture of the cooperative skills of SDN 94 Balla Kapubaten Enrekang (3) to get the description of the Effect of cooperative learning type STAD implementation on the ability of cooperation SDN 94 Balla Kapubaten Enrekang students. This type of research is a pre experimental experimental study involving one group of experiments with the design of the one group pretest-postest design. The dependent variable in this study is the ability of student cooperation and the independent variable is the implementation of cooperative learning type STAD. To find out the results of this study, researchers used the instrument of observation sheet and questionnaire a number of 13 statements. Observation sheet used to know the implementation of learning through the implementation of cooperative learning type STAD. Implementation of STAD type cooperative learning in learning IPS class V SD N 94 Balla Enrekang Regency consisting of 7 stages of Preparation of learning, Presentation of the material, group learning activities, examination of group outcomes, Students doing the test questions individually, testing and test results Group awards, as a whole for all three meetings of instructional activity can be said to be very well done. This is indicated by the average score of learning effectiveness of STAD type cooperative learning from the first meeting until the third meeting being in the categpry of very good. At the level of ability of student cooperation SDN 94 Balla Enrekang Regency on pretest and postest found that there is improvement of ability of student cooperation after given treatment in the form of cooperative learning type STAD of SDN 94 Balla Enrekang Regency. The result of test of hopotesis is known that there are difference of level of ability of student cooperation on pretest and posttest which is significant, it is shown from P-Value value so There is positive influence of STAD type cooperative learning in IPS class V SDN 94 Balla Kabupaten Enrekang